Dysfunction of CCR1+ decidual macrophages is a potential risk factor in the occurrence of unexplained recurrent pregnancy loss - Sang, Yifei; Li, Yanhong; Xu, Ling; Chen, Jiajia; Li, Dajin; Du, Meirong (Frontiers in Immunology, 2022)
Recurrent pregnancy loss (RPL) puzzles 1–3% of women of childbearing age worldwide. Immunological factors account for more than 60% of cases of unexplained RPL (URPL); however, the underlying mechanism remains unclear. Here, using single-cell sequencing data and functional experiments with clinical samples, we identified a distinct population of CCR1+ decidual macrophages (dMφ) that were preferentially enriched in the decidua from normal early pregnancies but were substantially decreased in patients with URPL. Specific gene signatures endowed CCR1+ dMφ with immunosuppressive and migration-regulatory properties, which were attenuated in URPL. Additionally, CCR1+ dMφ promoted epithelial-to-mesenchymal transition (EMT) to promote trophoblast migration and invasion by activating the ERK1/2 signaling pathway. Decidual stromal cell (DSC)-derived CCL8 was the key regulator of CCR1+ dMφ as CLL8 recruited peripheral CCR1+ monocytes, induced a CCR1+ dMφ-like phenotype, and reinforced the CCR1+ dMφ-exerted modulation of trophoblasts. In patients with URPL, CCL8 expression in DSCs was decreased and trophoblast EMT was defective. Our findings revealed that CCR1+ dMφ play an important role in immune tolerance and trophoblast functions at the maternal–fetal interface. Additionally, decreased quantity and dysregulated function of CCR1+ dMφ result in URPL. In conclusion, we provide insights into the crosstalk between CCR1+ dMφ, trophoblasts, and DSCs at the maternal–fetal interface and macrophage-targeted interventions of URPL.